In Silico Modelling Studies to Identification of Lead Compounds from Swietenia Macrophylla Against Cancer - M, Bhargavi; P, Harathi; B, Ajay Kumar; C, Anil Kumar Reddy; Kumar P, Praveen (Journal of Neonatal Surgery, 2025)
Objective: Cancer, a malignant neoplasm, is a multifactorial disease characterized by the progressive accumulation of genetic and epigenetic alterations. The present study aimed to identify potential lead compounds from Swietenia macrophylla with anticancer activity using molecular docking and in silico pharmacokinetic and toxicity profiling. Methods: Phytoconstituents of Swietenia macrophylla were identified and their structures retrieved from the PubChem database. Target proteins including Cyclin-Dependent Kinase-2 (PDB ID: 1DI8), Cyclin-Dependent Kinase-6 (PDB ID: 1XO2), Vascular Endothelial Growth Factor-2 (PDB ID: 2OH4), Anti-Apoptotic Protein (PDB ID: 2O2F), and Insulin Growth Factor (PDB ID: 2OJ9) were obtained from the Protein Data Bank. Molecular docking was performed using PyRx to evaluate binding affinity and interaction with active sites. Docking results were visualized using BIOVIA Discovery Studio Visualizer. Pharmacokinetic and toxicity parameters of the selected compounds were predicted using SWISS ADME and pkCSM tools. Results: The compounds Catechin, 3β-Hydroxystigmast-5-en-7-one, 3-Hydroxystigmast-5-en-7-one, and Epicatechin demonstrated strong binding affinity and favorable interactions, including hydrogen bonding and hydrophobic interactions with target proteins. These compounds also exhibited good pharmacokinetic properties and safety profiles. In comparison, standard anticancer drugs such as Seliciclib, Palbociclib, Lucitanib, Venetoclax, and Ceritinib showed similar binding interactions but demonstrated suboptimal pharmacokinetic and safety profiles. Conclusion: The study concludes that Catechin, 3β-Hydroxystigmast-5-en-7-one, 3-Hydroxystigmast-5-en-7-one, and Epicatechin are promising lead compounds from Swietenia macrophylla with potential application in cancer therapy